Sexual Satisfaction and its Associated Factors in Women with Candida Vaginitis: A Case-Control Study - Sareh Mehni; Hedyeh Askarpour; Neda Dastyar; Maryam Mirzaei; Akbar Mehralizadeh (مجله دانشگاه علوم پزشکی جیرفت, 2024)
Introduction: Candida vaginitis is a common disease in women which is accompanied by annoying symptoms in the genital area. Therefore, the present study was conducted with the aim of investigating the level of sexual satisfaction and its related factors in women with and without candida vaginitis.